DETERMINATION HETEROSIS,COMBINING ABILITY AND GENE ACTION USING HALF DIALLEL CROSSES IN MAIZE. - & abed, Hammadi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Six inbred lines of maize were crossed in this study by using half – diallel analysis method , during spring season of 2017, to produce fifteen F1 crosses. The parents and crosses were cultivated during fall season of 2017 by using R.C.B.D with three replications to determine heterosis, general and specific combining ability effects and gene action . Significant differences were found among parental and their crosses for all the traits . The results were showed that the hybrid ( Zm - 1× Zm - 5) had the highest heterosis in grain yield.plant-1 (113.4%). The hybrid (ART-B-17x SYN-33) produced highest number rows. ear-1 (17.9) rows, 500 kernel weight (112.9) gm and grain yield.plant-1 (214.7) gm . The values of specific combining ability variances were more than the general combining ability variances for all the traits, indicating that non-additive gene action was responsible for inheritance of all the traits. The values of the broad sense heritability for all characters were higher and average degree of dominance was exceeded one for all the traits . Results indicated that some inbreds could be used in breeding program to develop single crosses which have higher grain yield because all the traits under over dominance gene action